The Correlation between Metacognitive Strategies and Listening Comprehension - Nurhayati Nurhayati; Esther Mesly Eppang (Journal on Education, 2023)
This study was to determine the correlation between metacognitive strategies and listening comprehension. This study used quantitative designs, which were descriptive and correlational. This study's instruments were questionnaires adopted andergrifth, Goh, Mareschal, and Tafaghodtari (2006). This study was conducted to 63 students at Unklab Senior High School grade 11 Science enrolled in the first semester of the academic year 2021/2022. The sample of this study was taken by using total population sampling technique. Data were collected using two instruments and the data were analyzed by using pearson correlation. The result showed the correlation results obtained by the researchers were worth 0.00. Because the results obtained were less than 0.05, it was concluded that there was no correlation between metacognitive strategies and listening comprehension. And from the results found by researchers showed that the average respondents were weak in metacognitive strategies because based on the minimum completion criteria (kriteria ketuntasan minimal) of Unklab senior high school scores below 75 means that they failed.